Knowledge, Attitude and Practices towards Exclusive Breastfeeding among Lactating Mothers Presenting to Immunization Center, Holy Family Hospital, Rawalpindi, Pakistan - Muhammad Sheharyar Khan; Saqlain Ghazanfar; Abdur Rehman Malik; Faiqa Gull; Erej Fatima; Hina Sattar (Students’ Supplement of Journal of Rawalpindi Medical College, 2022)
Abstract Background: Suitable nourishment at the stage of infancy and during the early years of a child is essential to ensure children’s growth to their full potential. The World Health Organization (WHO) recommends exclusive breastfeeding for infants during the first six months after their birth, followed by breastfeeding in addition to complementary foods for up to two years of age or even after this period. Objectives: To determine the knowledge, attitude, and practices of mothers related to exclusive breastfeeding. Methods: This cross-sectional descriptive study was conducted at the immunization center, Holy Family Hospital, Rawalpindi. Women who were in the lactating phase in the past two years or already had children above two years of age were interviewed using a validated interviewer-administered questionnaire. Data were entered into SPSS version 23, and descriptive analysis was run. Results: The majority of the respondents belonged to 26-30 years (52.8%) and were housewives (83.0%). 96.6% of participants had heard of exclusive breastfeeding, and 44.9% had heard about it from health institutions. 88.0% believed that a child should get exclusive breastfeeding for at least six months. The majority thought that exclusive breastfeeding is better than artificial milk (93.1%), it is enough for six months (89.2%), and children fed under exclusive breastfeeding are relatively healthier (95.5%). 81.8% preferred exclusive breastfeeding in the first six months, but only 67.6% mothers practiced it. Conclusion: Our study found that most of the population had adequate knowledge and a positive attitude towards exclusive breastfeeding. Furthermore, a much greater proportion of people were practicing exclusive breast feeding as compared to previous years. Keywords: Exclusive breastfeeding, lactating mothers, knowledge, attitude, practices, breastfeeding, infants